2021
DOI: 10.11648/j.jfa.20210902.12
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Executive Share Ownership, Executive Compensation, and Independent Commissioners on Tax Avoidance

Abstract: Tax is a contribution that mandatory to be paid by personal and corporate taxpayers. The government used that tax for national development. Tax becomes a burden for companies that it is mandatory to be paid. If the companies got larger income so that the taxes that must be paid become larger too. On the other hand, if the companies got smaller income, the taxes that must be paid will become smaller. This leads the companies to avoid taxes that mandatory to be paid by reducing their amount of taxes. This is cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…From this explanation, it can be concluded that executive compensation has a significant negative effect on tax avoidance. The findings of this investigation agree with those of [9] and [10], but contrary to the findings of [11], [12], and [13] which showed executive compensation positive effect on tax avoidance. In other results in the table presented above, the significance value of Institutional Ownership (KI) is 0.076 which is greater than 0.05.…”
Section: H1supporting
confidence: 83%
See 4 more Smart Citations
“…From this explanation, it can be concluded that executive compensation has a significant negative effect on tax avoidance. The findings of this investigation agree with those of [9] and [10], but contrary to the findings of [11], [12], and [13] which showed executive compensation positive effect on tax avoidance. In other results in the table presented above, the significance value of Institutional Ownership (KI) is 0.076 which is greater than 0.05.…”
Section: H1supporting
confidence: 83%
“…From this explanation, it can be concluded that independent commissioners have no significant effect on tax avoidance. The findings of this investigation agree with those of [11] and [12], but contrary to the findings of [43] and [45] which showed independent commissioners have a positive effect on tax avoidance. Based on the table presented above, it can be found that the t-test results show an Accounting Conservatism significance value as big as 0.163 which is greater than 0.05.…”
Section: H1supporting
confidence: 73%
See 3 more Smart Citations